On OPr. pobanginnons (Ench. 69,1–2) as loan-rendition - Dini, Pietro U. (Baltistica, 2017)
The aim of this paper is to investigate how the expression zu fluchen bewegt (in the context: [Ich...] habe ſie erzrnet und zu fluchen bewegt) from the chapter on Confession in the Small Catechism by M. Luther was rendered in the Old Prussian, Old Lithuanian and Old Latvian translations. Usage and semantics of this expression as well as the different strategies employed by the translators in each language for translating it are studied in a contrastive way and by means of the hermeneutic method. Abel Will’s work was probably exposed to different impulses, among them literality and iconism. His translation process could have been influenced by both phonetic and semantic vicinity between German Woge, bewegen and bewegt bewogen. Contrastive examples in other languages are also given. According to the author, in the case of the OPr. word pobanginnons A. Will created a loan-rendition (Germ. Lehnschöpfung), a fact that reveals a subtle interference of German.